Aiaa Aviation 2020 Forum 2020
DOI: 10.2514/6.2020-2532
|View full text |Cite
|
Sign up to set email alerts
|

Sound Production due to Swirl-Nozzle Interaction: Model-Based Analysis of Experiments

Abstract: Indirect noise due to the interaction of flow inhomogeneities with a choked nozzle is as an important cause of combustion instability in solid rocket motors and is believed to be important in aircraft engines. A previously published experiment demonstrated that interaction of the nozzle with time-dependent axial swirl can also be a source of sound. This axial swirl was generated by intermittent circumferential mass injection upstream from a choked nozzle in a so-called Vortex Wave Generator. The present work d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Entropy inhomogeneities and vorticity patches induce so-called indirect combustion noise when passing through a choked nozzle referred to as entropy noise and vorticity noise, respectively. It was found that vorticity noise depends on the orientation of the vorticity viz., oriented normal or parallel to the axial main flow [130][131][132]. At the DLR's Engine Acoustics laboratory -using a dedicated experimental setup [131,132] -an experimental investigation of parallel component vorticity noise was performed [131,132].…”
Section: Main Flow Oriented Vorticity Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Entropy inhomogeneities and vorticity patches induce so-called indirect combustion noise when passing through a choked nozzle referred to as entropy noise and vorticity noise, respectively. It was found that vorticity noise depends on the orientation of the vorticity viz., oriented normal or parallel to the axial main flow [130][131][132]. At the DLR's Engine Acoustics laboratory -using a dedicated experimental setup [131,132] -an experimental investigation of parallel component vorticity noise was performed [131,132].…”
Section: Main Flow Oriented Vorticity Noisementioning
confidence: 99%
“…In the experiment, a time-dependent swirling flow was induced by unsteady tangential injection in a pipe upstream of a choked convergent-divergent nozzle. Theoretical analysis [130,132] found that as the resulting swirling flow passes through the nozzle, the axial stretching of the fluid causes an increase in rotation energy. The steady energy conservation in an isentropic flow (Bernoulli) implies a Mach number higher than unity at the throat and an associated reduction of density.…”
Section: Main Flow Oriented Vorticity Noisementioning
confidence: 99%
“…These are silent while advecting in the combustor but generate noise at the exhaust when interacting with the turbine blade rows [15]. This source of noise is termed indirect combustion noise and can be further decomposed as vortical [16][17][18], entropy [4,5] and, compositional noise [19][20][21] after the name of the flow perturbation which creates them. Entropy noise is believed to be its main component [9].…”
Section: Introductionmentioning
confidence: 99%